Cobalt chloride-induced oxidant-antioxidant imbalance in rat erythrocytes: The modulatory role of Kolaviron (2018)
Cobalt stimulates erythrocyte production via mechanisms that mimic physiological adaptations to hypoxic conditions. However, little is known about alterations in the balance of erythrocyte antioxidant defense system produced by cobalt. We investigated the effect of Kolaviron (KV) on cobalt chloride (CoCl2)-induced disturbances in erythrocyte antioxidant status and hematological parameters and compared the effects with those of Gallic acid (GA). Groups of rats were orally treated with either KV1 (100 mg/kg), KV2 (200 mg/kg) or GA (120 mg/kg), along with CoCl2 (350 ppm) in drinking water for 14 days. CoCl, produced significant (p<0.05) increases in packed cell volume, hemoglobin and red blood cell count, but no alterations in erythrocyte morphology, in the same way as rats treated with KV or GA. Significant (p<0.05) elevation in malondialdehyde (MDA) content and reductions in total thiols and reduced glutathione (GSH) in the CoCl2 group were indications of oxidative stress. KV produced significant (p<0.05) reduction in MDA, while restoring the levels of GSH and total thiols with elevations in" glutathione S-transferase and superoxide dismutase. Our results indicate that CoCl2-induced erythropoiesis was accompanied by altered antioxidant status of the erythrocytes. Kolaviron, however, ameliorated the disturbancesin erythrocyte antioxidant defense system.